A type of perfluorinated cationic resin, anion exchange membrane and membrane electrode based on Aza-Michael addition reaction
The synthesis of perfluorocation resins through Aza-Michael addition reaction solves the problem of degradation of traditional cationic resins under high-temperature alkaline conditions, and achieves the development of high-performance AEM, with a mild process and no toxic reagents are required.
Patent Information
- Application Number
- CN202210100904.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-27
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-01-27
AI Technical Summary
The existing cationic resins are prone to main chain degradation under high temperature alkali conditions, and the reagents used in the traditional chloromethylation process are toxic and unstable, making it difficult to meet the needs of high-performance AEM.
Perfluorocation resins were synthesized by Aza-Michael addition reaction, and cationic groups were directly grafted through a one-step method to avoid chloromethylation and quaternary amination processes. The reaction conditions were mild and the reaction degree was controllable.
The high alkali stability and high ionic conductivity of perfluorocation resins are achieved, which extends the service life of the membrane and avoids the use of toxic reagents.
Smart Images

Figure CN116554385B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, relates to a type of perfluorocation exchange resin and a synthesis method and application thereof, and in particular to a type of perfluorocation resin synthesized based on Aza-Michael addition reaction, as well as an anion exchange membrane and a membrane electrode. Background Art
[0002] Cationic resins are a type of high molecular weight functional materials that can conduct and exchange anionic groups. One of their important uses is the preparation of anion exchange membranes (AEMs) for use in fuel cells, electrodialysis, bipolar membranes, alkaline water electrolysis, and chemical high-efficiency separation fields.
[0003] At present, the commonly used strategy of synthetic cationic resin is to graft cationic groups on high molecular polymer matrix, first need to introduce chloromethyl group on polymer matrix in this process, and then obtain cationic groups by quaternization.But usually adopt chloromethyl ether and bischloromethyl ether as chloromethylating agent to carry out direct chloromethylation in chloromethylation process, or adopt formaldehyde, paraformaldehyde and hydrogen chloride or trimethylchlorosilane as chloromethylating agent to carry out indirect chloromethylation.Because the latter has defects such as low reactive activity, long reaction time, low productive rate, so the former is still mainstream technology (Chinese patent CN113471498A in current chloromethylation process; CN113042113A; CN113021877A).But, chloromethylating agents such as chloromethyl ether and bischloromethyl ether are unstable, volatile, irritant, corrosive, highly toxic, are two kinds of known carcinogenic compounds, and storage and transportation are difficult, so governments of various countries have issued relevant measures to forbid.
[0004] Based on this, more and more academic and industrial circles have proposed many strategies to avoid the use of chloromethyl ether and dichloromethyl ether (Chinese patents CN 101837253A; CN106220762A; CN108586745A), but the above chloromethylation process still inevitably uses other toxic chloromethylation reagents. In addition, the process of synthesizing cationic resins has many steps and the degree of reaction is difficult to control. Compared with perfluorosulfonic acid proton exchange membranes, AEM generally has the problem of low ion conductivity, and its performance cannot meet the requirements of ion membranes in the application process, which greatly limits the development of AEM.
[0005] At present, conventional cationic resins are all implemented based on hydrocarbon cationic polymers, such as polyethersulfone (CN106893103A), polyphenylene ether (J.Mater.Chem.A, 2018, 6, 15456-1547; Adv.Funct.Mater., 2018, 28, 1702758) or polystyrene (J.Membr.Sci., 2017, 536, 133-140; CN113471498A). However, as traditional main chains, polysulfone, polyether, and polyetherketone contain a large number of carbon-hydrogen bonds, such as -CH3, -CH2-, -CO, etc. Under high temperature and alkaline conditions, the β hydrogen atoms connected by the ion separation of these groups will be attacked by hydroxide ions and undergo Hoffman degradation, thereby causing the degradation and failure of the AEMs membrane. There is currently no commercial AEM membrane, so the development of a non-toxic and efficient cationic resin synthesis method and the preparation of an AEM with high stability and high ionic conductivity have become urgent problems to be solved.
[0006] The most widely used proton exchange membrane at present is the perfluorosulfonic acid polymer proton exchange membrane, which was invented by DuPont in the 1970s. Its molecular structure includes a perfluoro main chain skeleton -(CF2CF2)m-(CF2CF)n-, and a perfluoroether structure side chain with a sulfonic acid group (-SO3H) as the end group. m -(CF2CF) n-It has super chemical stability under alkaline conditions. Influenced by the successful application of PFSA, researchers have tried to use perfluorosulfonyl fluoride precursors (PFSO2F, Nafion-SO2F) to synthesize cationic polymers, such as literature (J.Mater.Chem., 2011, 21, 6158; J.Mater.Chem., 2013, 1, 1018-1021; J.Polym.Sci., Part B: Polym.Phys., 2019, 57, 700-712). However, on the one hand, since perfluorosulfonyl fluoride precursors are not soluble in conventional solvents, the reaction process is based on solid-liquid reaction, and the reaction degree is difficult to control. On the other hand, since the perfluoro skeleton has a strong electron-withdrawing ability, the ionic groups of the side groups are more easily attacked by hydroxides, resulting in chemical degradation and loss of ion conductivity (J. Membr. Sci., 2014, 467: 136-141; J. Mater. Chem. A., 2013, 1 1018-1021). At present, major countries in the world have begun to invest a lot of manpower and material resources in the research of high-performance AEM. At present, the perfluoro cationic resin based on PFSO2F and Nafion-SO2F cannot meet the requirements in all aspects such as anion conductivity, alkali resistance, and temperature resistance, especially the anion conductivity at high alkali concentration is far lower than 0.1S / cm, which can no longer meet the needs of ion conduction. Summary of the invention
[0007] The purpose of the present invention is to overcome the defects of the above-mentioned prior art, and to provide a type of perfluorocationic resin, anion exchange membrane and membrane electrode synthesized based on Aza-Michael addition reaction, in which no highly toxic reagent chloromethyl ether is required, the reaction conditions are mild, and the reaction degree can be effectively controlled. Different from the traditional Aza-Michael addition method, the method of the present invention does not require a catalyst and harsh reaction conditions, and can avoid the use of toxic solvents such as dichloromethane and acetonitrile.
[0008] The perfluoro cationic resin of the present invention has a perfluoro structure as the main chain structure, retaining the structural advantages of perfluoro ion polymers. Compared with the existing hydrocarbon main chain polymerization, the polymer of the present invention does not undergo main chain degradation under alkaline conditions, and electron-donating groups are introduced during the grafting of cationic groups, which can effectively improve the alkali stability and conductivity of the resin. The cationic groups can be directly grafted in a one-step method, without the need for chloromethylation and quaternization post-treatment processes. In addition, the process of introducing cations on the side chains is more effective, green and environmentally friendly, and the synthesis process is simple and effective.
[0009] The present invention also provides a type of anion exchange membrane and membrane electrode, which are prepared by synthesizing the perfluorocationic resin based on the Aza-Michael addition reaction. The obtained anion exchange membrane has high chemical stability and good ion conductivity. The electron-donating groups introduced into the side chains can weaken or slow down the electron-withdrawing ability of the main chain, thereby extending the service life of the ion membrane. The corresponding membrane electrodes are applied to fuel cells and alkaline water electrolysis, providing important membrane materials for further research and application of fuel cells and water electrolysis.
[0010] The purpose of the present invention can be achieved by the following technical solutions:
[0011] A type of perfluorinated cationic resin synthesized based on the Aza-Michael addition reaction, the structural formula is:
[0012]
[0013] The structure of formula (I) comprises an A unit (tetrafluoroethylene structural unit) and a B unit (perfluorocation structural unit);
[0014] Wherein, a is an integer of 1-30; preferably, a is an integer of 5-10;
[0015] Wherein, the B unit contains a perfluoroether group and a cationic group, and the structure of the perfluoroether group is shown in Formula II:
[0016]
[0017] In the formula, m is an integer of 0 to 10, preferably an integer of 0 to 3; n is an integer of 1 to 6, preferably an integer of 1 to 3; most preferably, m=0, 1; n=2; x is the number of repeating units, and x is 50 to 10,000.
[0018] Among them, at least one of the Ar1 or Ar2 structures of the B unit is a cationic group.
[0019] The cationic group structure contains one or more A group, the structure of which is shown in Formula III;
[0020]
[0021] The cationic group contains at least one (-CC-) group and connect.
[0022] Preferably, the cationic group structure is selected from one of Formula IV:
[0023]
[0024] Preferably, when only one of Ar1 or Ar2 is a cationic group, the other group is -H. When Ar1 and Ar2 are both cationic groups, the structures of Ar1 and Ar2 may be the same or different cationic groups.
[0025] According to the preferred embodiment of the present invention, the number average molecular weight of the perfluorocationic resin represented by formula (I) is 100,000 to 1,000,000, more preferably 200,000 to 600,000, and most preferably 200,000 to 400,000; the ion exchange capacity is 0.4 to 3.5 mmol / g, more preferably 0.8 to 2.5 mmol / g, and most preferably 0.90 to 1.8 mmol / g. The thermal degradation temperature is 265 to 290°C.
[0026] The present invention also provides a method for preparing the above-mentioned perfluorocationic resin, which is selected from one of the following methods:
[0027] (1) A perfluorosulfonamide polymer (PFSO2NH2) and a Y electrophilic monomer reagent containing a double bond undergo an Aza-Michael one-step addition reaction in an organic solvent, which can be self-catalytic or catalytic, to obtain a perfluorocationic resin; the Y monomer reagent contains one or more structure;
[0028] The structure of the Y monomer reagent is shown in Formula V, wherein at least one of R1 to R4 is a The remaining groups are one of -H, -OH, -CH3, -OCH3, -Ph (Ph represents a benzene ring), -OPh, -Cl, -CH2Cl, and -CH2CH3;
[0029]
[0030] Preferably, the structure of the Y monomer reagent is selected from one of the structures shown in Formula VI:
[0031]
[0032] (2) A perfluorosulfonamide polymer (PFSO2NH2) is subjected to an Aza-Michael addition reaction with a monomer reagent YY having a double bond and a chloromethyl group in a solvent to obtain a chloromethylated perfluorosulfonamide polymer, and then the chloromethylated perfluorosulfonamide polymer is subjected to a quaternization reaction with a reagent NN having a tertiary amine or tertiary phosphorus group to synthesize a perfluorocationic resin; the quaternization reaction can be self-catalyzed or catalyzed by adding a catalyst.
[0033] Preferably, the structure of the YY monomer reagent is as shown in Formula VII, wherein M1, M2, and M3 are respectively one of -H, -OH, -CH3, -OCH3, -Ph (Ph represents a benzene ring), -OPh, -Cl, -CH2Cl, and -CH2CH3; MN is -Ph, -OPh, or -(CH2) n -, wherein 20≥n≥0; X is one of F, Cl, Br, I;
[0034]
[0035] Further preferably, the structure of the YY monomer reagent is as shown in Formula VIII:
[0036]
[0037] Preferably, the NN reagent is a reagent containing a tertiary amine or tertiary phosphorus structure, and its general structural formula is shown in IX;
[0038]
[0039] Further preferably, the structure of the NN agent is one of the structures shown in Formula X:
[0040]
[0041] Preferably, the catalyst is selected from one of trimethylamine, N,N-diisopropylethylamine, 4-dimethylaminopyridine, triethanolamine, tetrabutylammonium bromide, triethylamine, AlCl3, potassium pyridine carbonate, ammonium carbonate and sodium carbonate.
[0042] Preferably, the preparation process of perfluorosulfonamide polymer (PFSO2NH2) refers to patents CN201510270702.6 and CN 201510094960.3.
[0043] Preferably, the solvent is at least one of N,N-dimethylformamide, deionized water, alcohol / water mixed solvent (alcohol is ethanol, n-propanol, isopropanol), N,N-dimethylacetamide, N-methylpyrrolidone, toluene, dichloromethane, chloroform, tetrahydrofuran, ethanol, n-propanol, isopropanol, dimethyl sulfoxide or ethyl acetate. Further preferably, the solvent is one of N,N-dimethylformamide, N,N-dimethylacetamide ethanol, n-propanol, and. Further preferably, the volume ratio of the alcohol / water mixed solvent is 1:1 to 3.
[0044] Preferably, in method (1), the molar ratio of PFSO2NH2 to reagent Y is 1:5-10.
[0045] Preferably, in method (2), the molar ratio of PFSO2NH2 to YY reagent is 1:5-15; the molar ratio of YY to NN reagent is 1:3-15.
[0046] Preferably, the reaction temperature in method (1) or (2) is 15-150°C, preferably 60-150°C; the reaction time is 1-48 hours, preferably 8-15 hours. Preferably, in method (2), the reaction temperature of PFSO2NH2 and YY reagent is 60-80°C, the time is 10 hours, and the reaction temperature of grafting NN monomer reagent is 80-150°C, 10-15 hours.
[0047] Preferably, the mass volume ratio of PFSO2NH2 to the organic solvent in method (1) or (2) is 1:1 to 30 g / mL; more preferably 1:1 to 25 g / mL; most preferably 1:1 to 20 g / mL.
[0048] Preferably, the reaction formula of method (1) is as follows:
[0049]
[0050] In method (1), Ar1 and Ar2 can be controlled to be -H or a cationic group by controlling the ratio of reactants and the selection of catalyst. The catalyst can regulate the addition reaction product to be a disubstituted product.
[0051] The reaction formula of method (2) is as follows:
[0052]
[0053] The ion exchange of the ion resin obtained by method (1) or (2) is determined based on the type of counter ion of the cation group. - Br - ,I - When alkali treatment is performed, it can be exchanged for OH - The alkali treatment process is to soak the obtained ion resin in a 2M KOH solution for 24 to 48 hours to completely convert the counter ions into OH - .
[0054] According to the requirements of product performance, the proportion of cationic groups in the polymer can be controlled by selecting the values of a, m, n, and the types of Y reagent, YY reagent, NN reagent, etc., thereby controlling the ion exchange capacity of the perfluorocationic polymer.
[0055] In addition, the present invention also provides a type of perfluoro cross-linked cationic resin based on Aza-Michael addition reaction, wherein the main chain structure of the repeating unit structure includes perfluorovinyl and perfluorovinyl ether, and the main chains are cross-linked by side chains, wherein the side chains contain two perfluoroether groups and two sulfonamide groups (-SO2NH or -SO2N), and at least one sulfonamide group is connected to a cationic group:
[0056] The structural formula of the perfluoro cross-linked cationic resin is as follows:
[0057]
[0058] In the formula, at least one of Ar1 and RR structures contains a cationic group; Ar1 is a cationic group or -H, and the RR structure is a structure after a bifunctional group reacts with an amino group, and the bifunctional structure is a structure containing two double bonds, two epoxy groups, two acyl chlorides, two chloromethyl groups, and two aldehyde groups.
[0059] The ion exchange capacity of the perfluoro cross-linked cationic resin is 0.5-1.0 mmol / g, the molecular weight is 200,000-1,000,000, and the thermal degradation temperature is 300-350°C.
[0060] Preferably, the RR structure is as follows -CH2CH2-Ph-CH2CH2-, -OC-Ph-CO-, -OC-CH2-CO-, -OC-(CH2)3-CO-, -OC-(CH2)4-CO-, -OC-(CH2)5-CO-, One of them.
[0061] Preferably, the number of cationic groups directly connected to the sulfonamide group is 1 to 3, more preferably 1 to 2.
[0062] in, The structure is:
[0063]
[0064] The present invention also provides a method for preparing the perfluoro cross-linked cationic resin based on the Aza-Michael addition reaction, wherein the preparation method is selected from one of the following methods:
[0065] Method 1:
[0066] (11) A perfluorosulfonamide polymer (PFSO2NH2) is subjected to an Aza-Michael one-step catalytic addition reaction with a Y electrophilic monomer reagent containing a double bond in an organic solvent to obtain a perfluoro cationic resin (such as Formula I), wherein Ar1 is a cationic group and Ar2 is -H;
[0067] (12) subjecting the reagent containing a bifunctional structure to an Aza-Michael reaction with the perfluorocationic resin obtained in step (11) in an organic solvent to obtain a perfluorocationic resin having a cross-linked structure;
[0068] The bifunctional reagent is selected from one of the following: CH2=CH-Ph-CH=CH2, ClOC-Ph-COCl, HOC-Ph-COH, HOOC-Ph-COOH, ClOC-CH2-COCl, ClOC-(CH2)3-COCl, Cl-OC-(CH2)4-CO-Cl, Cl-OC-(CH2)5-CO-Cl,
[0069] Preferably, the conditions such as the Y monomer reagent, the amount of organic solvent, the reaction temperature, the reaction time, etc. in method 1 are the same as those in the above-mentioned method for preparing the perfluorocationic resin.
[0070] Preferably, the catalyst is selected from one of trimethylamine, N,N-diisopropylethylamine, 4-dimethylaminopyridine, triethanolamine, tetrabutylammonium bromide, triethylamine, AlCl3, potassium pyridine carbonate, ammonium carbonate and sodium carbonate.
[0071] Preferably, the preparation process of perfluorosulfonamide polymer (PFSO2NH2) refers to patents CN201510270702.6 and CN 201510094960.3.
[0072] Preferably, the organic solvent is at least one of N,N-dimethylformamide, deionized water, an alcohol / water mixed solvent (the alcohol is ethanol, n-propanol, or isopropanol), N,N-dimethylacetamide, N-methylpyrrolidone, toluene, dichloromethane, chloroform, tetrahydrofuran, ethanol, n-propanol, isopropanol, dimethyl sulfoxide, or ethyl acetate.
[0073] Preferably, in step (11), the molar ratio of PFSO2NH2 to reagent Y is 1:5-10. The reaction temperature is 15-150°C, preferably 60-150°C; the reaction time is 1-48 hours, preferably 8-15 hours. The mass volume ratio of PFSO2NH2 to the organic solvent is 1:1-30 (g / ml); more preferably 1:1-25; most preferably 1:1-20.
[0074] Preferably, in step (12), the molar ratio of the perfluorocationic resin obtained in step (11) to the reagent containing a bifunctional structure is 1:5-10. The reaction temperature is 15-150°C, preferably 60-150°C; the reaction time is 1-48 hours, preferably 8-15 hours. The mass volume ratio of the perfluorocationic resin obtained in step (11) to the organic solvent is 1:1-30; more preferably 1:1-25; most preferably 1:1-20.
[0075] Method 2:
[0076] A perfluorosulfonamide polymer (PFSO2NH2) and a Y' electrophilic monomer reagent containing two double bonds undergo an Aza-Michael one-step autocatalytic addition reaction in an organic solvent or a catalytic addition reaction using a catalyst to obtain a perfluoro cross-linked cationic resin, wherein Ar1 is a -H or RR structure;
[0077] The Y' electrophilic monomer reagent contains at least one quaternary ammonium or quaternary phosphorus group, and the preferred structure is as follows:
[0078]
[0079] The temperature, reaction time and solvent dosage conditions are the same as those of the above-mentioned preparation method of perfluoro cationic resin. It should be noted that the reagent with cationic or bifunctional group in the present invention is in excess compared with the perfluorosulfonamide polymer (PFSO2NH2).
[0080] Preferably, the catalyst is selected from one of trimethylamine, N,N-diisopropylethylamine, 4-dimethylaminopyridine, triethanolamine, tetrabutylammonium bromide, triethylamine, AlCl3, potassium pyridine carbonate, ammonium carbonate and sodium carbonate.
[0081] Preferably, the preparation process of perfluorosulfonamide polymer (PFSO2NH2) refers to patents CN201510270702.6 and CN 201510094960.3.
[0082] Preferably, the organic solvent is at least one of N,N-dimethylformamide, deionized water, an alcohol / water mixed solvent (the alcohol is ethanol, n-propanol, or isopropanol), N,N-dimethylacetamide, N-methylpyrrolidone, toluene, dichloromethane, chloroform, tetrahydrofuran, ethanol, n-propanol, isopropanol, dimethyl sulfoxide, or ethyl acetate.
[0083] Preferably, the molar ratio of the PFSO2NH2 to the Y' reagent is 1:5-10. The reaction temperature is 15-150°C, preferably 60-150°C; the reaction time is 1-48 hours, preferably 8-15 hours. The mass volume ratio of PFSO2NH2 to the organic solvent is 1:1-30; more preferably 1:1-25; most preferably 1:1-20.
[0084] Method 3:
[0085] (31) A reagent containing a bifunctional structure is subjected to an Aza-Michael one-step catalytic addition reaction with a perfluorosulfonamide polymer (PFSO2NH2) in an organic solvent to obtain an ionic resin having a cross-linked structure, wherein Ar1 is H and RR is a cross-linked structure;
[0086] (32) subjecting the ionic resin having a cross-linked structure obtained in step (31) to an Aza-Michael reaction with a Y electrophilic monomer reagent containing a double bond in an organic solvent to obtain a perfluorocationic resin having a cross-linked structure, wherein Ar1 is a cationic group;
[0087] The bifunctional reagent is selected from one of the following: CH2=CH-Ph-CH=CH2, ClOC-Ph-COCl, HOC-Ph-COH, HOOC-Ph-COOH, ClOC-CH2-COCl, ClOC-(CH2)3-COCl, Cl-OC-(CH2)4-CO-Cl, Cl-OC-(CH2)5-CO-Cl,
[0088] Preferably, the catalyst is selected from one of trimethylamine, N,N-diisopropylethylamine, 4-dimethylaminopyridine, triethanolamine, tetrabutylammonium bromide, triethylamine, AlCl3, potassium pyridine carbonate, ammonium carbonate and sodium carbonate.
[0089] Preferably, the preparation process of perfluorosulfonamide polymer (PFSO2NH2) refers to patents CN201510270702.6 and CN 201510094960.3.
[0090] Preferably, the organic solvent is at least one of N,N-dimethylformamide, deionized water, an alcohol / water mixed solvent (the alcohol is ethanol, n-propanol, or isopropanol), N,N-dimethylacetamide, N-methylpyrrolidone, toluene, dichloromethane, chloroform, tetrahydrofuran, ethanol, n-propanol, isopropanol, dimethyl sulfoxide, or ethyl acetate.
[0091] Preferably, in step (31), the molar ratio of PFSO2NH2 to the reagent containing a bifunctional structure is 1:5-10. The reaction temperature is 15-150°C, preferably 60-150°C; the reaction time is 1-48 hours, preferably 8-15 hours. The mass volume ratio of PFSO2NH2 to the organic solvent is 1:1-30; more preferably 1:1-25; most preferably 1:1-20.
[0092] Preferably, in step (32), the molar ratio of the ionic resin with a cross-linked structure obtained in step (31) to the Y electrophilic monomer reagent containing a double bond is 1:5-10. The reaction temperature is 15-150°C, preferably 60-150°C; the reaction time is 1-48 hours, preferably 8-15 hours. The mass volume ratio of the ionic resin with a cross-linked structure obtained in step (31) to the organic solvent is 1:1-30; more preferably 1:1-25; most preferably 1:1-20.
[0093] The present invention also provides the use of the above-mentioned perfluoro cationic resin or perfluoro cross-linked cationic resin in one or more of the following: 1) use in the manufacture of fuel cells; 2) use in the preparation of membrane electrodes for alkaline water electrolysis; 3) use in electrodialysis; 4) use in seawater desalination; 5) use in antibacterial materials; 6) use in sewage treatment.
[0094] The present invention also provides an anion exchange membrane prepared based on the Aza-Michael addition reaction, wherein the anion exchange membrane component comprises the above-mentioned perfluorinated cationic resin or perfluorinated cross-linked cationic resin.
[0095] Preferably according to the present invention, the anion exchange membrane has an ion exchange capacity of 0.8 to 3.5 mmol / g, an ion conductivity of 40 to 300 mS / cm, a thermal degradation temperature of 260 to 350°C, and after a 6M KOH decay test for 500 hours, the ion exchange capacity retention rate is above 90%, and the ion conductivity retention rate is above 90%.
[0096] The preparation method of the anion exchange membrane is selected from one of the following, comprising the following steps:
[0097] (i) dissolving the perfluorocationic resin or perfluorocrosslinked cationic resin obtained by the above-mentioned Aza-Michael addition reaction in an organic solvent to prepare a perfluorocationic resin solution, and directly preparing a homogeneous anion exchange membrane by a solution casting method; or,
[0098] (ii) First, PFSO2NH2 is dissolved in an organic solvent and formed into a membrane by a solution casting method, and then the prepared membrane is subjected to an Aza-Michael addition reaction to prepare a heterogeneous anion exchange membrane.
[0099] Preferably, the concentration of the perfluoro cationic resin solution or the perfluoro cross-linked cationic resin in method (i) is 2-20 wt %, preferably 2-15 wt %.
[0100] Preferably, the organic solvent in method (i) or method (ii) is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, ethanol, ethanol / water mixed solvent, isopropanol / water mixed solvent, n-propanol / water mixed solvent, dimethyl sulfoxide or ethyl acetate.
[0101] Further preferably, the volume ratio of ethanol to water in the ethanol / water mixed solvent in method (i) or method (ii) is 3-7:7-3; the volume ratio of isopropanol to water in the n-propanol / water mixed solvent is 3-7:7-3.
[0102] Preferably, the solution casting method comprises the steps of coating a perfluorocationic resin solution or a PFSO2NH2 solution on a quartz surface dish, pre-drying at 80-90° C., drying at 140-150° C. for 90-100 min, and removing the solution from the mold.
[0103] The present invention also provides a membrane electrode used in alkaline water electrolysis and fuel cells, wherein the catalyst mixture component of the catalyst layer of the membrane electrode comprises the above-mentioned perfluoro cationic resin or perfluoro cross-linked cationic resin.
[0104] The method for preparing the membrane electrode comprises the following steps:
[0105] (1) dissolving the above-mentioned perfluoro cationic resin or perfluoro cross-linked cationic resin in a water / alcohol mixed solvent to prepare a 2-15 wt% solution, then adding a Pt / C or IrO2 catalyst to the solution and dispersing to obtain a catalyst mixture;
[0106] (2) using a spray gun to spray the catalyst mixture onto the hydrophobic treated gas diffusion layer to form a catalyst layer, and then heat treating to obtain an electrode layer;
[0107] (3) The electrode layers cut to a suitable size are placed on the upper and lower sides of the anion exchange membrane and processed by hot pressing to obtain a membrane electrode.
[0108] Preferably, the alcohol in the water / alcohol mixed solvent in step (1) is ethanol or isopropanol, and the volume ratio of water to alcohol is 3-7:7-3. Preferably, in step (1), ultrasonic dispersion is performed, and the ultrasonic time is 30-200 min. Preferably, in step (1), the concentration of the perfluorocationic resin solution is 2-15wt%.
[0109] Preferably, in step (2), the heat treatment temperature is 80-130°C and the time is 30-500 min. Preferably, in step (2), the dry weight content of IrO2 or Pt / C in the catalyst layer is 2.5 mg / cm 2 or 0.4 mg / cm 2 The dry weight content of perfluorinated cationic resin is 1.5 mg / cm 2 .
[0110] Preferably, the anion exchange membrane in step (3) is the anion exchange membrane of the present invention or other anion exchange membrane. Preferably, the pressure of the hot pressing treatment in step (3) is 0.1-5 MPa, the hot pressing temperature is 80-140° C., and the hot pressing treatment time is 30-150 s.
[0111] In the present invention, when preparing membrane electrodes for alkaline water electrolysis and fuel cells, the electrochemical properties of the membrane electrodes can be regulated by adjusting the proportion of each unit according to the requirements of product performance.
[0112] Beneficial effects:
[0113] The above-mentioned type of perfluorocationic resin, anion exchange membrane and membrane electrode synthesized based on Aza-Michael addition reaction provided by the present invention has the following advantages over the previously proposed perfluorocationic polymer (CN105037604A, CN104710639A):
[0114] (1) The present invention is based on the Aza-Michael addition reaction to synthesize perfluoro cationic resin, which does not require chloromethylation and quaternization processes. The reaction conditions are mild, and the cationic group can be directly grafted onto the polymer side chain in one step. In addition, the reaction process does not require the use of a catalyst, and the reaction degree can be effectively controlled.
[0115] (2) The Aza-Michael synthesis of perfluorocationic resin is based on the addition reaction between amino groups and double bonds. Only one or two H are added to the connecting structure. The molecular weight in the repeating unit is low, and the ion exchange capacity is higher, which is beneficial to improve the ion conductivity. In addition, the YY and Y reagents described in the present invention are commercial reagents, which are convenient and easy to obtain and are easy to promote commercialization.
[0116] (3) The resin obtained by the present invention has a high ion exchange capacity (0.8-3.5 mmol / g); the cationic resin synthesized by the present invention, the A and B units in the perfluoro cationic resin can regulate the ion conductivity and ion exchange capacity of the anion exchange membrane. After the perfluoro cationic resin prepared by the present invention is subjected to an alkali decay test for 500 hours, the ion exchange capacity (IEC) retention rate is as high as 91% or more, proving that the obtained resin has a high ability to resist hydroxyl attack, the thermal degradation temperature is higher than 260°C, and can reach up to 310.5°C. The ultra-stable perfluoro skeleton structure can effectively improve the service life of the perfluoro cationic polymer and its products. Compared with the uncrosslinked cationic resin, the crosslinked cationic resin has further improved mechanical properties and thermal stability.
[0117] (4) The anion exchange membrane obtained by the present invention has a high ion conductivity (40-300mS / cm) in the range of 10°C to 80°C. At 80°C, the ion conductivity is 50-245mS / cm, while the conductivity of most anion membranes currently is less than 10mS / cm. It also has excellent alkali resistance and temperature resistance, and a thermal degradation temperature greater than 270°C, which can reach up to 318.6°C. The anion exchange membrane and the corresponding membrane electrode provided by the present invention can be used in fuel cells and alkaline water electrolysis. The anion exchange membrane of the present invention has a high ion conductivity in a large temperature range (10°C to 100°C), and after being tested by a 6M KOH decay test for 500h, the ion conductivity retention rate is above 90%.
[0118] (5) The membrane electrode provided by the present invention uses the ion resin or ion membrane prepared by the present invention as raw material, which can effectively improve the service life of the membrane electrode. The performance test results of the membrane electrode show that at open circuit voltage (OCV), 30% relative humidity (RH) and 90°C, the duration of the membrane electrode of the present invention can reach more than 220h, and the membrane electrode power density reaches 1020.5mWcm -2 , which is nearly three times of the prior art, indicating that the membrane electrode of the present invention has a higher conversion efficiency; the electrolytic water membrane electrode at 1.0A / cm 2 The required electrolysis voltage is 1.62V, indicating that the membrane electrode has lower energy loss. BRIEF DESCRIPTION OF THE DRAWINGS
[0119] Figure 1 It is the infrared spectrum of PFSO2NH2 and the target product A1 in Example 1.
[0120] Figure 2 The conductivity of the anion exchange membrane prepared in Example 2 changes within the temperature range of 10°C to 80°C.
[0121] Figure 3 This is a graph showing the ion conductivity retention rate of the anion exchange membrane prepared in Example 2. DETAILED DESCRIPTION
[0122] The present invention is described in detail below in conjunction with specific examples, which are only used to illustrate the present invention in detail and are not used to limit the scope of protection of the present invention. The present invention is not limited to the following embodiments, and other combination schemes derived on the basis of the present invention all belong to the scope of protection of the present invention. The raw materials and reagents involved in the examples, unless otherwise specified, are all common commercially available products; the experimental methods involved in the examples, unless otherwise specified, are all conventional technical means in the art.
[0123] The wavy line of the present invention represents an alkyl chain or perfluoroalkyl chain of any length, and may also contain a benzene ring, etc. The length is schematic and does not represent the actual length.
[0124] In the embodiment, a 6M KOH decay experiment is used to accelerate the attack of the target product to achieve the purpose of examining the chemical stability of the target product. The chemical stability of the target product is evaluated by testing the retention rate (RV%) of the ion exchange capacity (IEC) of the target product before and after the decay experiment.
[0125] The specific conditions of the alkaline decay experiment are as follows: the target product is immersed in a 6M KOH solution and maintained at 80°C for 500 hours, during which the KOH solution is replaced every 3 hours. After the experiment, the product is taken out and washed with deionized water several times, and finally dried at 60°C for 4 hours.
[0126] Titration of ion exchange capacity (IEC): Accurately weigh a certain weight of the dry target product, and then use a 1M NaCl aqueous solution for ion exchange for more than 12 hours. Collect the ion exchange solution, use phenolphthalein as an indicator, and titrate with 0.1M NaOH standard solution until the solution turns pink. The ion exchange capacity (IEC) value of the target product can be calculated according to the following formula:
[0127] IEC=(V NaOH ×C NaOH ) / m
[0128] Where: V NaOH ——The volume of NaOH standard solution consumed, mL; C NaOH ——molar concentration of NaOH standard solution, mmol / mL; m——mass of dry target product, g.
[0129] Ion Exchange Capacity (IEC) Retention:
[0130] RV%=(IEC1-IEC0) / IEC0
[0131] Wherein: IEC1 and IEC0 represent the ion exchange capacity (IEC) of the target product before and after the Fenton experiment, respectively.
[0132] Anion exchange membrane ion conductivity determination: The two-electrode method was used to test the resistance R of the sample. The instrument used was the electrochemical workstation Autolab PGSTA302. The frequency range was 106Hz-10Hz. The conductivity was calculated using the formula:
[0133] σ=L / RS
[0134] Where: L is the thickness of the membrane (cm), R is the resistance of the membrane (Ω), σ is the conductivity of the sample (S / cm), S is the test area of the sample (cm 2 ).
[0135] Anion exchange membrane conductivity retention rate:
[0136] RV%=(σ1-σ0) / σ0
[0137] Where: σ1 and σ0 represent the ionic conductivity of the anion exchange membrane before and after the Fenton experiment, respectively.
[0138] Thermal degradation temperature (defined as the temperature at which the polymer degrades by 5%): The test was conducted using a thermogravimetric analyzer, TAQ50 produced by Perkin Elmer, USA, with N2 atmosphere, a heating rate of 10°C / min, and a temperature range of 50-800°C. The samples were dried at 60°C for 24h before testing.
[0139] Membrane electrode performance for water electrolysis membrane:
[0140] A multi-channel electrochemical workstation was used to control the battery voltage and current. During the test, a preheated 1 M KOH solution was added at 5 mL min -1 The flow rate was 50°C and the temperature was maintained at 50°C. The polarization curve (current density vs. voltage) was tested with a scanning voltage range of 1.3-2.5 V and a scanning rate of 5 m V s -1 Before recording the first polarization curve, the cell was activated for a period of time under a varying current. Using the chronopotentiometry, the cell was tested at 50 °C and 1 mol L -1 KOH, 200 mA cm -2 The battery stability is tested at the current density. The test is terminated when the battery voltage changes by more than 0.2V during the entire test.
[0141] Fuel cell membrane performance test:
[0142] The fuel cell membrane electrode was assembled into a single cell and tested on a fuel cell workstation. Humidified hydrogen and oxygen were introduced into the anode and cathode of the single cell respectively (flow rate 50mL / min), and the discharge power density of the H2-O2 fuel cell was tested at 80% relative humidity (RH) and 80°C. Among them, the fuel of the anode is pure hydrogen, and the oxidant of the cathode is oxygen, and the flow rate is controlled to 50mL / min. Before the battery test, the membrane electrode was activated by running in 0.01A constant current mode for 1-3 hours. After the output voltage stabilized, the battery polarization curve was measured by linear voltage scanning.
[0143] The durability or chemical stability of the membrane electrode samples was evaluated at open circuit voltage (OCV) at 30% RH and 90°C, with hydrogen and air gas flow rates of 3.43 slpm and 8.37 slpm, respectively. The OCV of each cell in the stack was monitored over time. When the OCV of any of the five cells in the stack reached 0.8 V or the H2Crossover was greater than 10 mA / cm 2 , end the test.
[0144] Example 1
[0145] A type of perfluorinated cationic resin synthesized based on the Aza-Michael addition reaction, using 1-allyl-3-methylimidazolium chloride (M W =158.63) as a Y monomer reagent to carry out an Aza-Michael one-step addition reaction to synthesize the target resin; PFSO2NH2 resin (a is 7; m=1, n=2, number average molecular weight is 400,000, molar equivalent Ew=1100 g / mol) is reacted to synthesize the target product, and the specific steps are as follows:
[0146] A 500mL sealed reactor was cleaned, evacuated, and replaced with high-purity nitrogen three times, and then 10g PFSO2NH2 resin and 200mL dry N, N-dimethylacetamide were added, the stirring device was turned on, and it was slowly heated to 80°C. After it was completely dissolved, 0.04g of 1-allyl-3-methylimidazolium chloride was added, and the molar ratio of PFSO2NH2 to 1-allyl-3-methylimidazolium chloride was about 1:10; after the addition was completed, Aza-Michael reaction was carried out at 80°C with mechanical stirring, and cooled to room temperature after 12 hours. The product was filtered, and the unreacted 1-allyl-3-methylimidazolium chloride was removed by washing with deionized water for several times. Finally, it was immersed in a 2M KOH solution for 24 hours to completely convert chloride ions into hydroxide ions. The target product obtained is recorded as A1, and the reaction formula is as follows:
[0147]
[0148] The target product A1 was subjected to infrared transmission spectrum measurement. Figure 1 is PFSO2NH2 and A1( Figure 1 The infrared characterization result of curve B) is shown in the figure. It can be seen that the -1 and 1548cm -1 The characteristic peaks of PFSO2NH2 primary amine (-NH2 group) are between 1548cm -1 The characteristic peak of primary amine belonging to PFSO2NH2 completely disappeared, proving that the primary amine group fully participated in the reaction; at the same time, the peak at 3000-3200cm -1 -CH-, -CH2, -CH3 appeared at 1751cm -1 The characteristic front of CN and the 752cm -1 The characteristic peak of the imidazole ring is located at the position assigned to the reference Journal of Membrane Science 362 (2010) 97-104; the above results prove that the perfluorocationic resin A1 is successfully synthesized by a one-step addition reaction.
[0149] The IEC of the target product A1 was 0.81 mmol / g after ion exchange capacity (IEC) measurement. The theoretical E of the target product A1 can be obtained from the Ew of PFSO2NH2 resin = 1100 g / mol. W =1100+158.63-18.5=1240g / mol, where 158.63 is the molar equivalent of 1-allyl-3-methylimidazolium chloride; 18.5 is Cl -1 With OH -1 The molar equivalent difference between the two groups is calculated by referring to the formula of Chem.Rev.2004,104,4535-4585. According to the theoretical EW, the theoretical IEC=1000 / 1240mmol / g=0.81mmol / g can be obtained. The value obtained by titration is close to the theoretical IEC value, which proves that all the amino groups in PFSO2NH2 participate in the reaction after the Aza-Michael reaction. Based on this, the experimental data of the present invention are all monitored by titration IEC to monitor the Aza-Michael reaction process.
[0150] Example 2
[0151] A type of perfluorinated anion exchange membrane prepared based on Aza-Michael addition reaction, the specific steps are as follows:
[0152] The target product A1 prepared in Example 1 was dissolved in N,N-dimethylformamide to prepare an 8 wt% perfluoro cationic resin solution, and then the resin solution was coated on a clean and smooth quartz surface dish, pre-dried at 80°C, placed in an oven at 145°C for 90 minutes, taken out and demolded, to prepare a perfluoro anion exchange membrane.
[0153] The ion exchange capacity IEC of the anion exchange membrane is 0.81 mmol / g as measured by titration.
[0154] The above anion exchange membrane was tested for ion conductivity in water at 10℃~80℃. The results are as follows Figure 2 As shown in the figure, the ionic conductivity shows an approximately linear growth trend with the increase of temperature, mainly because the movement rate of ions becomes faster at high temperatures. From 10℃ to 80℃, the conductivity of the ion membrane increases from 41.6mS / cm to 112.8mS / cm.
[0155] After 80 days of alkaline attenuation test, the ion conductivity and ion exchange capacity retention rate of the above ion membrane were both as high as over 90%, proving that the obtained anion exchange membrane has a high ability to resist hydroxide attack, improving the alkaline stability of the anion exchange membrane and effectively extending its service life.
[0156] Example 3
[0157] One type of perfluorinated cationic resin is synthesized based on the Aza-Michael addition reaction, and the specific steps are as follows:
[0158] The synthesis process is referred to Example 1, except that allyl trimethyl ammonium chloride (M W =135.64) as a Y monomer reagent to carry out an Aza-Michael one-step addition reaction to synthesize the target resin, the number average molecular weight of PFSO2NH2 is 350,000; the synthesized target product is recorded as A2, and the IEC of the obtained target product A2 is 0.82mmol / g after IEC measurement. The reaction formula is as follows:
[0159]
[0160] Example 4
[0161] The preparation of the perfluorinated anion exchange membrane based on the Aza-Michael addition reaction is as follows:
[0162] The target product A2 prepared in Example 3 was dissolved in a n-propanol / water mixed solvent (volume ratio 1:1) to prepare a 6 wt% perfluorocationic resin solution, and then the resin solution was coated on a clean and smooth quartz surface dish, pre-dried at 80°C, placed in an oven at 145°C for 90 minutes, taken out and demolded, to prepare a perfluoroanion exchange membrane.
[0163] The anion exchange capacity IEC of the anion exchange membrane was determined by titration to be 0.81 mmol / g, and the ion conductivity of the membrane in 80° C. water was 120.5 mS / cm.
[0164] Example 5
[0165] One type of perfluorinated cationic resin is synthesized based on the Aza-Michael addition reaction, and the specific steps are as follows:
[0166] The synthesis process is referred to Example 1, except that a in the PFSO2NH2 resin is 7; m=0, n=2, the number average molecular weight is 420,000, and the molar equivalent Ew=866 g / mol) is subjected to a one-step addition reaction to synthesize the target resin. During the reaction, trimethylamine is added as a catalyst, and the molar ratio of 1-allyl-3-methylimidazolium chloride to trimethylamine is about 1:10; the synthesized target product is recorded as A3, and after IEC determination, the IEC of the obtained target product A2 is 1.74 mmol / g. The reaction formula is as follows:
[0167]
[0168] Example 6
[0169] A type of perfluoro anion exchange membrane prepared based on Aza-Michael addition reaction, the ion membrane preparation process refers to Example 4, the difference is that A3 is dissolved in an isopropanol / water mixed solvent (volume ratio 1:1) to prepare a 6wt% perfluoro cationic resin solution.
[0170] The anion exchange capacity IEC of the anion exchange membrane was determined by titration to be 1.72 mmol / g, and the ion conductivity of the membrane in 80° C. water was 242.4 mS / cm.
[0171] Example 7
[0172] One type of perfluorinated cationic resin is synthesized based on the Aza-Michael addition reaction, and the specific steps are as follows:
[0173] The synthesis process is referred to Example 3, except that a in the PFSO2NH2 resin is 8; m=0, n=2, the number average molecular weight is 420,000, and the molar equivalent Ew=966 g / mol) is subjected to a one-step addition reaction to synthesize the target resin. During the reaction, triethylamine is added as a catalyst, and the molar ratio of allyltrimethylammonium chloride to triethylamine is about 1:10; the synthesized target product is recorded as A4, and after IEC determination, the IEC of the obtained target product A4 is 1.66 mmol / g, and the reaction formula is as follows:
[0174]
[0175] Example 8
[0176] A type of perfluoro anion exchange membrane prepared based on Aza-Michael addition reaction, the ion membrane preparation process is as follows: first, the PFSO2NH2 in Example 7 is selected and dissolved in an organic solvent to prepare a 6wt% perfluoro PFSO2NH2 solution, and then the resin solution is coated on a clean and smooth quartz surface dish, pre-dried at 80°C, placed in an oven at 145°C for 90 minutes, taken out and demolded to prepare a PFSO2NH2 membrane; then the prepared membrane is immersed in a 10% aqueous solution of 1-allyl-3-methylimidazolium chloride, and finally triethylamine is added to the solution as a catalyst; Aza-Michael addition reaction is carried out at 60°C, and after the reaction is completed for 24 hours, the 1-allyl-3-methylimidazolium chloride remaining on the membrane surface is washed with deionized water to obtain a perfluoro anion membrane, and its structural formula is the same as A4.
[0177] The anion exchange capacity IEC of the anion exchange membrane was determined by titration to be 1.67 mmol / g, and the ion conductivity of the membrane in 80° C. water was 210.7 mS / cm.
[0178] Example 9
[0179] A type of perfluorinated cationic resin synthesized based on the Aza-Michael addition reaction, using 4-vinylbenzyl chloride (M W =152.62) as the YY monomer reagent, trimethylamine as the NN monomer reagent (M W =59.11), Aza-Michael two-step addition reaction was performed to synthesize the target resin; PFSO2NH2 resin (a is 7; m=0, n=2, number average molecular weight is 400,000, molar equivalent Ew=866g / mol) was reacted to synthesize the target product, and the specific steps are as follows:
[0180] A 500mL sealed reactor was cleaned, evacuated, and replaced with high-purity nitrogen three times, and then 10g PFSO2NH2 resin and 200mL dry N, N-dimethylacetamide were added. The stirring device was turned on and slowly heated to 80°C. After it was completely dissolved, 0.04g of 4-vinylbenzyl chloride was added, and the molar ratio of PFSO2NH2 to 4-vinylbenzyl chloride was about 1:10; finally, 0.16g of trimethylamine was added (the molar ratio of 4-vinylbenzyl chloride to trimethylamine was about 1:10;). After the addition was completed, Aza-Michael reaction was carried out at 80°C under mechanical stirring. After 12 hours, it was cooled to room temperature, and the product was filtered. After multiple washings with deionized water, unreacted 4-vinylbenzyl chloride and trimethylamine were removed. Finally, it was immersed in a 2M KOH solution for 24 hours to completely convert chloride ions into hydroxide ions. The obtained target product was recorded as A5. After IEC determination, the IEC of the obtained target product A4 was 0.94mmol / g. The reaction formula is as follows:
[0181]
[0182] Example 10
[0183] A type of perfluoro anion exchange membrane prepared based on Aza-Michael addition reaction. The ion membrane preparation process refers to Example 4, except that the A5 product is used to prepare the perfluoro cationic resin solution. The obtained anion exchange membrane has an ion exchange capacity IEC of 0.93 mmol / g as measured by titration, and the ion conductivity of the membrane in 80°C water is 142.5 mS / cm.
[0184] Embodiment 11
[0185] A method for synthesizing a perfluoro cross-linked cationic resin based on an Aza-Michael addition reaction, wherein the synthesis process is referred to Example 5, except that diallyldimethylammonium chloride (M W =161.67) as a bifunctional Y monomer reagent to carry out Aza-Michael one-step addition reaction to synthesize a perfluoro cross-linked cationic resin, and no catalyst is added during the synthesis process. The synthesized target product is recorded as A6. After IEC measurement, the IEC of the obtained target product A6 is 0.53 mmol / g. The reaction formula is as follows:
[0186]
[0187] in, The structure is:
[0188]
[0189] Example 12
[0190] A type of perfluoro anion exchange membrane prepared based on Aza-Michael addition reaction. The ion membrane preparation process refers to Example 8, except that the prepared PFSO2NH2 membrane is soaked in a 10% aqueous solution of diallyldimethylammonium chloride, and no catalyst is needed. The Aza-Michael addition reaction is carried out at 60°C. After the reaction is completed for 24 hours, the diallyldimethylammonium chloride remaining on the membrane surface is washed with deionized water to obtain a perfluoro anion membrane, and its structural formula is the same as A6.
[0191] The anion exchange capacity IEC of the anion exchange membrane was determined by titration to be 0.52 mmol / g, and the ion conductivity of the membrane in 80° C. water was 50.3 mS / cm.
[0192] Example 13
[0193] A preparation method of a membrane electrode for a fuel cell prepared by an Aza-Michael addition reaction, the specific steps are as follows:
[0194] (1) The target product A3 in Example 5 was dissolved in a water / n-propanol (volume ratio of 3:7) mixed solvent to prepare a 5 wt% perfluorocationic polymer solution, and then 10 mL of the perfluorocationic polymer solution was added to a Pt / C catalyst, and ultrasonicated for 100 min to obtain a catalyst mixture;
[0195] (2) The catalyst mixture of step (1) was sprayed onto the 2 cm×2 cm gas diffusion layer that had been hydrophobically treated using a spray gun to form a catalyst layer. After heat treatment at 130° C. for 90 min, the platinum loading on the catalyst layer surface was 0.4 mg / cm 2 , an electrode layer consisting of a gas diffusion layer and a catalyst layer is obtained, and the obtained electrode layer is divided into a hydrogen electrode and an oxygen electrode due to the difference in contact with fuel hydrogen and oxygen in the membrane electrode;
[0196] (3) The hydrogen electrode and oxygen electrode cut to appropriate sizes are placed on the upper and lower sides of the anion exchange membrane (3 cm×3 cm) in Example 6, aligned and matched well, and then subjected to hot pressing treatment with a press having a pressure of 0.8 MPa, a hot pressing temperature of 140°C, and a duration of 60 s. The press is opened, and after natural cooling, the membrane electrode for fuel cells prepared based on the Aza-Michael addition reaction is obtained.
[0197] Embodiment 14
[0198] The preparation of a membrane electrode for water electrolysis prepared by an Aza-Michael addition reaction comprises the following specific steps:
[0199] (1) The target product A3 in Example 5 was dissolved in a water / isopropanol (volume ratio of 2:8) mixed solvent to prepare a 5 wt% perfluoro ion polymer solution, and then two groups of 10 mL of the perfluoro ion polymer solution were added with Pt / C and IrO2 catalysts respectively, and ultrasonicated for 100 min to obtain a catalyst mixture; IrO2 was used as the anode catalyst and Pt / C was used as the cathode in the alkaline water electrolysis device;
[0200] (2) The catalyst mixture of step (1) was sprayed onto the 2 cm×2 cm gas diffusion layer after hydrophobic treatment using a spray gun to form a catalyst layer. After heat treatment at 130° C. for 90 min, the dry weight contents of IrO2 and Pt / C in the catalyst layer were 2.5 mg / cm 2 and 0.4mg / cm 2 , obtaining an electrode layer consisting of a gas diffusion layer and a catalyst layer.
[0201] (4) The membrane electrode cut to a suitable size is placed on the upper and lower sides of the anion membrane (3 cm×3 cm) in Example 2, aligned and matched perfectly, and then subjected to hot pressing treatment with a press. The pressure of the press is 0.8 MPa, the hot pressing temperature is 140°C, and the duration is 60 s. The press is opened, and after natural cooling, the membrane electrode for water electrolysis prepared based on the Aza-Michael addition reaction is obtained.
[0202] Comparative Example 1
[0203] A perfluorinated cationic resin and anion exchange membrane prepared by a non-Aza-Michael addition reaction, the specific steps are as follows:
[0204] Glycidyl trimethylammonium chloride (GCI) and PFSO2NH2 resin (a is 7; m=1, n=2, number average molecular weight is 400,000, molar equivalent Ew=1100 g / mol) are selected to react and synthesize the target product. The specific steps are as follows:
[0205] After cleaning the 100mL reactor, add 50mL of dry N,N-dimethylformamide, turn on the stirring device, evacuate and replace with high-purity nitrogen three times, then add 0.1g of GCI, slowly heat to 60℃, and add 30g of PFSO2NH2 resin after it is completely dissolved. The molar ratio of PFSO2NH2 to GCI is about 1:10. React at 80℃ with mechanical stirring for 10h, then cool to room temperature, filter the product, wash with deionized water to remove unreacted GCI, and finally soak in 2M KOH solution for 24h to completely convert chloride ions into hydroxide ions. The product is dried at 60℃ to obtain the target product, recorded as A7. The reaction formula is as follows:
[0206]
[0207] The target product A7 was measured by ion exchange capacity (IEC), and the IEC was 0.78 mmol / g.
[0208] A7 was dissolved in dimethyl sulfoxide to prepare an 8 wt% perfluorocationic resin solution, and then the resin solution was coated on a clean and smooth quartz surface dish, pre-dried at 80°C, placed in an oven at 145°C for 90 minutes, taken out and demolded, and an anion exchange membrane was prepared.
[0209] The ion exchange capacity IEC of the anion exchange membrane was measured by titration to be 0.77 mmol / g.
[0210] The ion conductivity of the anion exchange membrane at 80° C. is 72.5 mS / cm.
[0211] The perfluorocationic resin A7 obtained by the method has a similar structure to the perfluorocationic resin A2 obtained by the method of the present invention, but the ion conductivity of the corresponding anion exchange membrane obtained is quite different. The conductivity of the perfluoroanion exchange membrane prepared by A2 of the present invention is 120.5 mS / cm, which is much higher than the conductivity of the anion exchange membrane prepared by A7. The main reason is that hydroxyl substituents are introduced into the structure of the cationic resin obtained by the method, which increases the molar equivalent of the resin, resulting in a lower IEC, thereby reducing the conductivity of the anion exchange membrane.
[0212] The pyrolysis temperature of the perfluorocationic resin prepared by the method is lower than that of the perfluorocationic resin and the perfluoroanion exchange membrane prepared by the method of the present invention, indicating that the perfluorocationic resin and the perfluoroanion exchange membrane prepared by the method of the present invention have higher thermal stability. The IEC retention rate (%) of the perfluorocationic resin A2 prepared by the method of the present invention after 500h of the alkali decay experiment is 93.5%, while the IEC retention rate (%) of the fluorinated cationic resin A7 prepared by the method of comparative example 1 after 500h of the alkali decay experiment is only 80.2%, indicating that the perfluorocationic resin prepared by the method of the present invention has stronger chemical stability and service life.
[0213] Comparative Example 2
[0214] A composite anion exchange membrane prepared by a non-Aza-Michael addition reaction is prepared. The 1-allyl-3-methylimidazolium chloride in Example 1 is directly added to a PFSO2NH2 resin (a is 7; m=1, n=2, number average molecular weight is 400,000, and molar equivalent Ew=1100 g / mol), and the mixture is evenly mixed by mechanical stirring. The molar proportion of the mixed solution is 15%. The obtained mixed solution is coated on a clean and smooth quartz surface dish, pre-dried at 80°C, and then dried in an oven at 145°C for 90 minutes. The mixed solution is taken out and demolded to prepare a composite anion exchange membrane.
[0215] The ion exchange capacity (IEC) of the obtained anion exchange membrane was measured to be 0.12 mmol / g.
[0216] The ion conductivity of the composite anion exchange membrane at room temperature (25° C.) is 5.5 mS / cm.
[0217] Comparative Example 3
[0218] A non-Aza-Michael addition reaction is used to prepare a membrane electrode for a fuel cell. The specific steps are as follows:
[0219] (1) The perfluorocationic resin A7 of Comparative Example 1 was diluted in a mixed solvent of isopropanol / water (volume ratio of 8:2) to prepare a 5 wt% perfluorocationic polymer solution, and then 10 mL of the above solution was added to a Pt / C catalyst, and ultrasonicated for 100 min to obtain a catalyst mixture;
[0220] (2) The membrane electrode slurry of step (1) was sprayed onto the 2 cm×2 cm gas diffusion layer that had been hydrophobically treated using a spray gun to form a catalyst layer. After heat treatment at 130° C. for 90 min, the platinum loading on the catalyst layer surface was 0.4 mg / cm 2 , an electrode layer consisting of a gas diffusion layer and a catalyst layer is obtained, and the obtained electrode layer is divided into a hydrogen electrode and an oxygen electrode due to the difference in contact with fuel hydrogen and oxygen in the membrane electrode;
[0221] (4) Place the hydrogen electrode and oxygen electrode cut to appropriate sizes on the upper and lower sides of the anion exchange membrane (3 cm×3 cm) in step comparative example 1, align them up and down and fit them well, and perform hot pressing on them with a press. The pressure of the press is 0.8 MPa, the hot pressing temperature is 140°C, and the duration is 60 seconds. Open the press, and take out the prepared membrane electrode after natural cooling.
[0222] Comparative Example 4
[0223] A preparation method of a membrane electrode for water electrolysis prepared by a non-Aza-Michael addition reaction, the specific steps are as follows:
[0224] (1) The target product A7 in Comparative Example 1 was dissolved in a water / n-propanol (volume ratio of 3:7) mixed solvent to prepare a 5 wt% perfluoro ion polymer solution, and then two groups of 10 mL of the perfluoro ion polymer solution were added with Pt / C and IrO2 catalysts respectively, and ultrasonicated for 100 min to obtain a catalyst mixture; IrO2 was used as the anode catalyst and Pt / C was used as the cathode in the alkaline water electrolysis device;
[0225] (2) The catalyst mixture of step (1) was sprayed onto the 2 cm×2 cm gas diffusion layer after hydrophobic treatment using a spray gun to form a catalyst layer. After heat treatment at 130° C. for 90 min, the dry weight contents of IrO2 and Pt / C in the catalyst layer were 2.5 mg / cm 2 and 0.4mg / cm 2 , obtaining an electrode layer consisting of a gas diffusion layer and a catalyst layer.
[0226] (4) The membrane electrode cut to a suitable size is placed on the upper and lower sides of the anion membrane (3 cm×3 cm) in Comparative Example 1, aligned and matched perfectly, and then subjected to hot pressing treatment with a press. The press pressure is 0.8 MPa, the hot pressing temperature is 140°C, and the duration is 60 seconds. The press is opened, and the membrane electrode for water electrolysis is taken out after natural cooling.
[0227] Performance Testing:
[0228] The perfluorocationic resin, anion exchange membrane and membrane electrode prepared above were tested for performance, and the results are shown in Tables 1 to 3:
[0229] Table 1. Alkali stability test results of perfluorinated cationic resin
[0230] IEC retention rate after 500h of alkaline decay test (%) Thermal degradation temperature(℃) Example 1 93.5 280.7 Example 3 93.2 285.6 Example 5 91.4 270.3 Example 7 91.6 268.5 Example 9 96.6 270.5 Embodiment 11 94.6 310.5 Comparative Example 1 80.2 260.8
[0231] As can be seen from Table 1, the IEC of the perfluorocationic resin synthesized in the present invention is above 90% after 500h of the alkali decay experiment, and the thermal degradation temperature is also above 260°C. In particular, the cross-linked resin in Example 11 has the best thermal stability, and the thermal degradation temperature reaches 310°C, indicating that the introduction of the cross-linked structure can effectively improve the thermal stability of the resin; the resin containing the conjugated benzene ring structure in Example 9 has the highest IEC retention rate, indicating that the introduction of the conjugated structure can effectively improve the chemical stability of the resin; in addition, the IEC retention rate and thermal degradation temperature of the resin obtained in all examples are significantly improved compared with the resin synthesized by non-Aza-Michael addition reaction, indicating that the perfluorocationic resin prepared by the present invention has high chemical stability, and the purpose of regulating the thermal stability and chemical stability of the resin can be achieved by regulating the unit structure.
[0232] Table 2. Performance test results of perfluorinated anion exchange membrane
[0233]
[0234] As can be seen from Table 2, the anion exchange membrane prepared by the perfluorocationic resin synthesized by the Aza-Michael addition reaction has an ion conductivity retention rate of more than 90% after 500 hours of alkaline decay experiment, and the thermal degradation temperature of the anion exchange membrane is more than 270°C; compared with the anion exchange membrane prepared by non-Aza-Michael addition reaction (comparative example), the chemical stability and thermal stability of the ion exchange membrane are significantly improved, and the service life of the ion membrane is effectively extended. In particular, the conductivity of the ion membrane in Example 6 is the highest, reaching 242.4 mS / cm, indicating that the introduction of the diionic group can effectively improve the ion conductivity of the membrane; the ion membrane containing the conjugated benzene ring structure in Example 10 has the highest conductivity retention rate, indicating that the introduction of the conjugated structure can effectively improve the chemical stability of the ion membrane; the cross-linked ion membrane in Example 12 has the best thermal stability, indicating that the introduction of the cross-linked structure can further effectively improve the thermal stability of the ion membrane, wherein Comparative Example 2 is to directly add small molecules to conventional perfluoropolymers to prepare a composite anion exchange membrane. Although small molecules can directly conduct hydroxide ions, small molecules are easy to agglomerate and lose and have poor compatibility with polymers, which leads to a decrease in the mechanical properties and conductivity of the anion exchange membrane, but affects its electrochemical properties.
[0235] Table 3. Performance test results of membrane electrode
[0236]
[0237] As shown in Table 3, the membrane electrode prepared by Aza-Michael addition reaction can last for more than 220 hours at open circuit voltage (OCV), 30% relative humidity (RH) and 90°C, while the membrane electrode (Comparative Examples 3 and 4) using non-Aza-Michael addition reaction lasts for less than 100 hours, indicating that the durability of the membrane electrode prepared by the present invention has been effectively improved. In addition, the power density of the fuel cell membrane electrode prepared by Aza-Michael addition reaction reached 1020.5mWcm -2 , which is nearly three times that of Example 3, indicating that the membrane electrode has a higher conversion efficiency; the electrolytic water membrane electrode is at 1.0A / cm 2 The required electrolysis voltage is 1.62 V, which is lower than that of Comparative Example 4, indicating that the membrane electrode has lower energy loss.
Claims
1. A method for preparing a perfluorocationic resin based on an Aza-Michael addition reaction, characterized in that: The structural formula of perfluorinated cationic resin is: The structure of formula (I) comprises a tetrafluoroethylene structural unit A and a perfluorocation structural unit B; wherein a is an integer of 1 to 30, and x is 50 to 10000; The structural unit B contains a perfluoroether group and a cationic group, and the structure of the perfluoroether group is shown in Formula II: In the formula, m is an integer of 0 to 10, and n is an integer of 1 to 6; at least one of the Ar1 or Ar2 structures is a cationic group; and the preparation method is selected from one of the following methods: (1) A perfluorosulfonamide polymer PFSO2NH2 and a Y electrophilic monomer reagent containing a double bond undergo an Aza-Michael one-step addition reaction in an organic solvent, which can be self-catalytic or catalytic, to obtain a perfluoro cationic resin; the Y electrophilic monomer reagent contains one or more structure; The structure of the electrophilic monomer reagent Y is shown in Formula V, wherein at least one of R1 to R4 is a The remaining groups are one of -H, -OH, -CH3, -OCH3, -Ph, -OPh, -Cl, -CH2Cl, and -CH2CH3; (2) A perfluorosulfonamide polymer PFSO2NH2 is subjected to an Aza-Michael addition reaction with a monomer reagent YY having a double bond and a chloromethyl group in a solvent to obtain a chloromethylated perfluorosulfonamide polymer, and then the chloromethylated perfluorosulfonamide polymer is subjected to a quaternization reaction with a reagent NN having a tertiary amine or tertiary phosphorus group to synthesize a perfluorocationic resin, and the quaternization reaction can be self-catalyzed or catalyzed by adding a catalyst; The structure of the YY monomer reagent is shown in Formula VII, wherein M1, M2, and M3 are respectively one of -H, -OH, -CH3, -OCH3, -Ph, -OPh, -Cl, -CH2Cl, and -CH2CH3; MN is -Ph, -OPh, or -(CH2) n -, wherein 20≥n≥0; X is one of F, Cl, Br, I; The NN reagent is a reagent containing a tertiary amine or tertiary phosphorus structure, and its general structural formula is shown in IX; 2. The method for preparing the perfluorocationic resin according to claim 1, characterized in that: The cationic group has at least one -CC- group and one or more The connected group has a structure as shown in Formula III; 3. The method for preparing the perfluorocationic resin according to claim 2, characterized in that: The cationic group structure is selected from one of Formula IV:
4. The method for preparing the perfluorocationic resin according to claim 1, characterized in that: a is an integer of 5 to 10; m is an integer of 0 to 3; n is an integer of 1 to 3; The number average molecular weight of the perfluorocationic resin shown in formula (I) is 100,000 to 1,000,000; the ion exchange capacity is 0.4 to 3.5 mmol / g; and the thermal degradation temperature is 265 to 290°C.
5. The method for preparing the perfluorocationic resin according to claim 1, characterized in that: The catalyst is selected from one of trimethylamine, N,N-diisopropylethylamine, 4-dimethylaminopyridine, triethanolamine, tetrabutylammonium bromide, triethylamine, AlCl3, potassium pyridine carbonate, ammonium carbonate and sodium carbonate; The solvent is selected from at least one of N,N-dimethylformamide, deionized water, ethanol / water mixed solvent, n-propanol / water mixed solvent, isopropanol / water mixed solvent, N,N-dimethylacetamide, N-methylpyrrolidone, toluene, dichloromethane, chloroform, tetrahydrofuran, ethanol, n-propanol, isopropanol, dimethyl sulfoxide or ethyl acetate; In method (1), the molar ratio of PFSO2NH2 to reagent Y is 1:5-10; In method (2), the molar ratio of PFSO2NH2 to YY reagent is 1:5-15; the molar ratio of YY to NN reagent is 1:3-15; In method (1) or (2), the reaction temperature is 15 to 150° C. and the reaction time is 1 to 48 hours. In method (1) or (2), the mass volume ratio of PFSO2NH2 to the organic solvent is 1:1 to 30 g / mL.
6. The method for preparing the perfluorocationic resin according to claim 5, characterized in that: The solvent is selected from one of N,N-dimethylformamide, N,N-dimethylacetamide, ethanol and n-propanol; the reaction temperature required in method (1) or (2) is 60 to 150°C; the reaction time required is 8 to 15 hours; the mass volume ratio of PFSO2NH2 to the organic solvent in method (1) or (2) is 1:1 to 25 g / mL.
7. The method for preparing the perfluorocationic resin according to claim 6, characterized in that: In method (1) or (2), the mass volume ratio of PFSO2NH2 to the organic solvent is 1:1 to 20 g / mL.
8. A type of perfluoro cross-linked cationic resin based on Aza-Michael addition reaction, characterized in that: The main chain structure of the repeating unit structure includes perfluorovinyl and perfluorovinyl ether, and the main chains are cross-linked by side chains, wherein the side chains contain two perfluoroether groups and two sulfonamide groups, at least one sulfonamide group is connected to a cationic group, and the sulfonamide group is -SO2NH or -SO2N; The structural formula of the perfluoro cross-linked cationic resin is as follows: in, The structure is: Wherein Ar1 is a cationic group or -H, and the RR structure is a structure after the reaction of a bifunctional group and an amino group, wherein the bifunctional structure is a structure containing two double bonds, two epoxy groups, two acyl chlorides, two chloromethyl groups, and two aldehyde groups; wherein at least one of the Ar1 and RR structures contains a cationic group; The RR structure is selected from -CH2CH2-Ph-CH2CH2-, -OC-Ph-CO-, -OC-CH2-CO-, -OC-(CH2)3-CO-, -OC-(CH2)4-CO-, -OC-(CH2)5-CO-, One of; The number of cationic groups directly connected to the sulfonamide group is 1 to 3.
9. The perfluorinated cross-linked cationic resin according to claim 8, characterized in that: The number of cationic groups directly connected to the sulfonamide group is 1 to 2.
10. The method for preparing the perfluoro cross-linked cationic resin according to claim 8, characterized in that: The preparation method is selected from one of the following methods: Method 1: (11) A perfluorosulfonamide polymer PFSO2NH2 is subjected to an Aza-Michael one-step catalytic addition reaction with a Y electrophilic monomer reagent containing a double bond in an organic solvent to obtain a perfluoro cationic resin as shown in Formula I, wherein Ar1 is a cationic group and Ar2 is -H; (12) subjecting the reagent containing a bifunctional structure to an Aza-Michael reaction with the perfluorocationic resin obtained in step (11) in an organic solvent to obtain a perfluorocationic resin having a cross-linked structure; The bifunctional reagent is selected from one of the following: CH2=CH-Ph-CH=CH2, ClOC-Ph-COCl, HOC-Ph-COH, HOOC-Ph-COOH, ClOC-CH2-COCl, ClOC-(CH2)3-COCl, Cl-OC-(CH2)4-CO-Cl、Cl-OC-(CH2)5-CO-Cl、 Method 2: A perfluorosulfonamide polymer PFSO2NH2 and a Y' electrophilic monomer reagent containing two double bonds and at least one quaternary ammonium or quaternary phosphorus group undergo an Aza-Michael one-step autocatalytic addition reaction in an organic solvent or a catalytic addition reaction using a catalyst to obtain a perfluoro cross-linked cationic resin, wherein Ar1 is a -H or RR structure; Method 3: (31) A reagent containing a bifunctional structure is subjected to an Aza-Michael one-step catalytic addition reaction with a perfluorosulfonamide polymer PFSO2NH2 in an organic solvent to obtain an ionic resin having a cross-linked structure, wherein Ar1 is H and RR is a cross-linked structure; (32) subjecting the ionic resin having a cross-linked structure obtained in step (31) to an Aza-Michael reaction with a Y electrophilic monomer reagent containing a double bond in an organic solvent to obtain a perfluorocationic resin having a cross-linked structure, wherein Ar1 is a cationic group; The bifunctional reagent is selected from one of the following: CH2=CH-Ph-CH=CH2, ClOC-Ph-COCl, HOC-Ph-COH, HOOC-Ph-COOH, ClOC-CH2-COCl, ClOC-(CH2)3-COCl, Cl-OC-(CH2)4-CO-Cl, Cl-OC-(CH2)5-CO-Cl, 11. Use of the perfluorocationic resin prepared by the method of any one of claims 1 to 7 or the perfluorocrosslinked cationic resin of claim 8 in one or more of the following: 1) in the manufacture of fuel cells; 2) in the preparation of membrane electrodes for alkaline water electrolysis; 3) in electrodialysis; 4) in seawater desalination; 5) in antibacterial materials; 6) in sewage treatment.
12. An anion exchange membrane prepared based on Aza-Michael addition reaction, characterized in that: The anion exchange membrane component comprises a perfluoro cationic resin prepared by the method according to any one of claims 1 to 7 or a perfluoro cross-linked cationic resin according to claim 8.
13. A membrane electrode for alkaline water electrolysis or fuel cell, characterized in that: The catalyst mixture component of the catalyst layer of the membrane electrode comprises the perfluorocationic resin prepared by the method according to any one of claims 1 to 7 or the perfluorocrosslinked cationic resin according to claim 8.
Citation Information
Patent Citations
Polyaryletherketone ketone anion-exchange membrane containing phthalazinone structure and preparation method thereof
CN101837253A
Preparation method of perfluorinated sulfonamide-based anion exchange membrane
CN104710639A
A method for preparing a perfluorosulfonamide anion exchange membrane
CN104710639B
Short chain perfluorosulfonamide anion ionomer for fuel cells, preparation and applications thereof
CN105037604A
Short-chain perfluorosulfonamide anionic ionomers for fuel cells, their preparation and application
CN105037604B